Methods of communicative competence formation of future specialists in the field of law during the study of psychological and pedagogical disciplines - KOZHEMIAKO, Natalija (Journal of Education, Technology and Computer Science, 2013)
The article deals with methods of communicative competence future lawyer in the study of psychological and pedagogical disciplines.